(untitled) (Research, Society and Development, 2023)
The objective of this study is to conduct a systematic review of the literature on the indiscriminate use of the drug Sildenafil Citrate in young people. To this end, data from the do Portal de Periódicos da Coordenação de Aperfeiçoamento de Pessoal de Nível Superior (CAPES) is used, covering a time frame of five years (2018-2022) in Portuguese, English or Spanish languages. Thus, we aim to analyze how the literature has addressed the high consumption of Sildenafil Citrate by young people aged 15 to 29 years, especially because it is a drug that does not require medical prescription retention and has gone through patent infringement. With this, we conclude that the indiscriminate use of Sildenafil Citrate by young people can have serious consequences, such as cardiovascular problems, headaches, visual changes, nausea and even priapism (prolonged and painful erection), in addition to bringing a social and cultural impact to society.